2023
DOI: 10.1212/con.0000000000001232
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Cerebral Small Vessel Disease

Abstract: OBJECTIVECerebral small vessel disease (CSVD) is a common neurologic condition that contributes to considerable mortality and disability because of its impact on ischemic and hemorrhagic stroke risk and dementia. While attributes of the disease have been recognized for over two centuries, gaps in knowledge remain related to its prevention and management. The purpose of this review is to provide an overview of the current state of knowledge for CSVD.LATEST DEVELOPMENTSCSVD can be recognized by well-defined radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…CSVD contributes to morbidity and mortality through increasing ischemic and hemorrhagic stroke risk and association with cognitive decline and dementia. 4 Studies have demonstrated similar prevalence rates between men and women; however, women are more likely to have acute stroke presentations. There is limited evidence for strong differences across racial and ethnic groups, although some studies suggest that Black and Hispanic patients presenting with intracerebral hemorrhage (ICH) have a greater CSVD burden.…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…CSVD contributes to morbidity and mortality through increasing ischemic and hemorrhagic stroke risk and association with cognitive decline and dementia. 4 Studies have demonstrated similar prevalence rates between men and women; however, women are more likely to have acute stroke presentations. There is limited evidence for strong differences across racial and ethnic groups, although some studies suggest that Black and Hispanic patients presenting with intracerebral hemorrhage (ICH) have a greater CSVD burden.…”
Section: Epidemiologymentioning
confidence: 99%
“…Some data also suggest that sociodemographic factors, including lower education in childhood, are associated with worse CSVD. 4 HYPERTENSION Duration and lifetime exposure to hypertension remain two of the most important independent modifiable risk factors in the development of CSVD in long-term prospective population studies. Lipohyalinosis, a process of wall thickening and luminal narrowing with fibrinoid necrosis, is thought to be the primary mechanism by which hypertension causes CSVD.…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations